Verbal Aggression of Social Media Users Among Adolescents in Terms of Loneliness and Self-Control - Ma’ruf, Fajri; Noviekayati, IGAA; Santi, Dyan Evita (PT FORMOSA CENDEKIA GLOBAL, 2025)
Verbal aggression refers to the act of attacking others through hurtful words or communication. Various factors can contribute to verbal aggression, including loneliness and self-control. This study aims to explore the connection between loneliness, self-control, and verbal aggression among social media users. Using a quantitative approach with a survey method, the research targets students of SMK Negeri 1 Tambusai, encompassing a total population of 724 students. A purposive sampling technique was applied to select participants. Data were gathered using measurement scales for verbal aggression, loneliness, and self-control. The analysis was conducted using multiple regression techniques with SPSS version 25. The findings from the analysis revealed an F value of 145.137 with a significance level of 0.000 (p<0.05). These results indicate that loneliness and self-control have a significant influence on verbal aggression among adolescent social media users.